2022
DOI: 10.4240/wjgs.v14.i9.1060
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy, stump closure and endoloops: A meta-analysis

Abstract: BACKGROUND Acute appendicitis (AA) is one of the main indications for urgent surgery. Laparoscopic appendectomy (LA) has shown advantages in terms of clinical results and cost-effectiveness, even if there is still controversy about different devices to utilize, especially with regards to the endoloop (EL) vs endostapler (ES) when it comes to stump closure. AIM To compare safety and cost-effectiveness of EL vs ES. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Several reports have discussed methods of appendectomy in laparoscopic surgery [ 21 23 ]. Zorzetti N et al suggested the routine use of endloop for appendectomy even in case with complicated appendicitis because of cost effectivity and lower complications [ 21 , 22 ]. Bao W et al reported that purse-string sutures effectively reduced the incidence of postoperative complications after a laparoscopic appendectomy for CA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have discussed methods of appendectomy in laparoscopic surgery [ 21 23 ]. Zorzetti N et al suggested the routine use of endloop for appendectomy even in case with complicated appendicitis because of cost effectivity and lower complications [ 21 , 22 ]. Bao W et al reported that purse-string sutures effectively reduced the incidence of postoperative complications after a laparoscopic appendectomy for CA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only if the appendix is mobilized, a clip, loop, or stapler can be used depending on the base thickness [ 17 ]. A recently performed meta-analysis showed that endoloops and endostaplers are safe for appendix stump closure and have no difference in postoperative complication rate [ 31 ]. While self-locking polymeric clips (also known as Hem-o-Lok clips) are a less prevalent option in laparoscopic appendectomy for stump closure and are more used for the closure of bleeding vessels or tissue structures [ 16 ], they were also proven to have advantages: They are safe, cheap, and easy to use [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appendectomy techniques in laparoscopic surgery have been covered in a number of studies. Because endloop surgery is less expensive and has fewer problems than open surgery, Zorzetti N et al recommended using it routinely for surgery, especially in cases of severe appendicitis (13) (14) . Pursestring sutures have been shown by Bao W et al to be an effective way to lower the incidence of postoperative problems after a laparoscopic appendectomy for CA (15) .…”
Section: Laparoscopic Appendectomymentioning
confidence: 99%